Morbid Obesity in Women Is Associated with an Altered Intestinal Expression of Genes Related to Cancer Risk and Immune, Defensive, and Antimicrobial Response - Ho-Plágaro, Ailec; Rodríguez-Díaz, Cristina; Santiago-Fernández, Concepción; López-Gómez, Carlos; García-Serrano, Sara; Martín-Reyes, Flores; Rodríguez-Pacheco, Francisca; Rodríguez-Cañete, Alberto; Alcaín-Martínez, Guillermo; Vázquez-Pedreño, Luis; Valdés, Sergio; Garrido-Sánchez, Lourdes; et al. (Biomedicines, 2022)
Background: Little is known about the relation between morbid obesity and duodenal transcriptomic changes. We aimed to identify intestinal genes that may be associated with the development of obesity regardless of the degree of insulin resistance (IR) of patients. Material and Methods: Duodenal samples were assessed by microarray in three groups of women: non-obese women and women with morbid obesity with low and high IR. Results: We identified differentially expressed genes (DEGs) associated with morbid obesity, regardless of IR degree, related to digestion and lipid metabolism, defense response and inflammatory processes, maintenance of the gastrointestinal epithelium, wound healing and homeostasis, and the development of gastrointestinal cancer. However, other DEGs depended on the IR degree. We mainly found an upregulation of genes involved in the response to external organisms, hypoxia, and wound healing functions in women with morbid obesity and low IR. Conclusions: Regardless of the degree of IR, morbid obesity is associated with an altered expression of genes related to intestinal defenses, antimicrobial and immune responses, and gastrointestinal cancer. Our data also suggest a deficient duodenal immune and antimicrobial response in women with high IR.